2020
DOI: 10.1016/j.resuscitation.2020.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-like presentation in OHCA creates barriers to dispatch recognition of cardiac arrest

Abstract: Purpose: Early recognition of out-of-hospital cardiac arrest (OHCA) by 9-1-1 dispatchers is a critical first step along the resuscitation pathway. Barriers to recognition may lead to adverse outcomes among patients. This study aims to determine the impact of seizure-like activity among OHCA patients during 9-1-1 calls. Methods: We evaluated a retrospective cohort study of all adult, non-traumatic OHCAs that occurred prior to emergency medical services (EMS) arrival on scene in a major metropolitan area from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
8
0
5
Order By: Relevance
“…25,27 A recent observational study including 3502 OHCAs identified 149 (4.3%) victims with seizure-like activity. 28 Patients presenting with seizurelike activity were younger (54 vs. 66 years old; p < 0.05), were more likely to have a witnessed arrest (88% vs. 45%; p < 0.05), more likely to present with an initial shockable rhythm (52% vs. 24%; p < 0.05), and more likely to survive to hospital discharge (44% vs. 16%; p < 0.05). Similar to agonal respiration, seizures complicate the recognition of cardiac arrest for both lay people and professionals (median time to dispatcher identification of the cardiac arrest; 130 s vs. 62 s; p < 0.05).…”
Section: Seizuresmentioning
confidence: 97%
See 1 more Smart Citation
“…25,27 A recent observational study including 3502 OHCAs identified 149 (4.3%) victims with seizure-like activity. 28 Patients presenting with seizurelike activity were younger (54 vs. 66 years old; p < 0.05), were more likely to have a witnessed arrest (88% vs. 45%; p < 0.05), more likely to present with an initial shockable rhythm (52% vs. 24%; p < 0.05), and more likely to survive to hospital discharge (44% vs. 16%; p < 0.05). Similar to agonal respiration, seizures complicate the recognition of cardiac arrest for both lay people and professionals (median time to dispatcher identification of the cardiac arrest; 130 s vs. 62 s; p < 0.05).…”
Section: Seizuresmentioning
confidence: 97%
“…Similar to agonal respiration, seizures complicate the recognition of cardiac arrest for both lay people and professionals (median time to dispatcher identification of the cardiac arrest; 130 s vs. 62 s; p < 0.05). 28 Recognising cardiac arrest after a seizure episode when the victim remains unresponsive with abnormal breathing is important to prevent delayed CPR. The risk of delaying CPR for a cardiac arrest victim far outweighs any risk from performing CPR on a person not in cardiac arrest.…”
Section: Seizuresmentioning
confidence: 99%
“…The main obstacle of recognizing OHCA was the difficulty of determining the patient's respiratory status for bystanders [12]. Another important reported symptom of cardiac arrest in our study was seizure-like activity, which may mislead the call handler from recognizing cardiac arrest to epilepsy as in the study of Vaillancourt et al [5], [13].…”
Section: Discussionmentioning
confidence: 65%
“…In einer jüngeren Beobachtungsstudie konnten 3502 Patienten registriert werden, die außerhalb eines Krankenhauses/präklinisch einen Kreislaufstillstand erlitten hatten und krampfähnliche Bewegungen gezeigt hatten (OHCA). 4,3 % ( n = 149) zeigten krampfähnliche Aktivitäten [ 31 ]. Diese Patienten waren jünger (54 vs. 66 Jahre, p < 0,05), hatten häufiger einen beobachteten Kreislaufstillstand (88 vs. 45 %, p < 0,005), wurden eher in einem defibrillierbaren Rhythmus angetroffen (52 vs. 24 %, p > 0,05 und überlebten öfter bis zur Entlassung aus dem Krankenhaus (44 vs. 16 %).…”
Section: Evidenz Die Den Leitlinien Zugrunde Liegtunclassified
“…Ähnlich wie bei der Schnappatmung führten krampfähnliche Episoden bei einem nicht reagierenden, nicht normal atmenden Patienten zu Problemen beim Erkennen des Kreislaufstillstands durch Laien/Notfallzeugen und Leitstellendisponenten. (Mittlere Zeit bis zur Wahrnehmung des Kreislaufstillstands durch den Leitstellendisponenten (130 s vs. 62 s, p > 0,05) [ 31 ].…”
Section: Evidenz Die Den Leitlinien Zugrunde Liegtunclassified